Thursday

August 28, 2014

August 28, 2014

Posted by **Dave** on Tuesday, January 2, 2007 at 6:11pm.

Prove:

(tanx + secx -1)/(tanx - secx + 1)= tanx + secx

My work so far:

(sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x - 1/cosx + cosx/cosx)= tanx + cosx

(just working on the left side)

((sinx + 1 - cosx)/cosx)/((sinx - 1 + cosx)/cosx)

((sinx + 1 - cosx)/cos x) x (cos x/(sinx - 1 + cosx))

(sinx + 1 - cosx)/(sinx - 1 + cosx)

here is where I get stuck. Could someone point me in the right direction?

**Related Questions**

Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...

precal - 1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-...

Simplifying with Trigonometry Identities - Hi, I am a senior in High School ...

Math - Im really struggling with these proving identities problems can somebody ...

Mathematics - Trigonometric Identities - Prove: (tanx)(sinx) / (tanx) + (sinx...

Mathematics - Trigonometric Identities - Prove: sinx + tanx = tanx (1 + cosx) ...

maths - trigonometry - I've asked about this same question before, and someone ...

Pre-Calculus - How do you verify: 1.) sinxcosx+sinx^3secx=tanx 2.) (secx+tanx)/(...

Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...

math - 1. (sinx/cscx)+(cosx/secx)=1 2. (1/sinxcosx)-(cosx/sinx)=tanx 3. (1/1+cos...